PREVALENCE OF FIBULARIS TERTIUS MUSCLE IN A SCOTTISH POPULATION: A DISSECTION STUDY - Andrés S. Parodi Feye; Clare Lamb (Asociación Argentina de Anatomía Clínica, 2023)
Fibularis tertius (FT) is a muscle of the anterior compartment of the leg that is considered inconstant, whose reported prevalence varies widely among populations. The current work aims to determine the prevalence of FT in a Scottish population. Forty-four caucasian cadavers of Scottish origin (88 lower limbs; 19 females, 25 males; age at death: 81.8 ± 11.2 years), preserved using the Thiel soft-fix embalming method were analyzed. The absence of FT was observed in 5 of the cadavers studied (11.4%). In four male cadavers the absence was verified unilaterally; in one female cadaver the absence was verified bilaterally. Taking into account the total number of lower limbs, FT was absent from 6.8% of cases, determining a total prevalence of 93.2%. There were no significant differences in the presence or absence of FT when comparing lower limbs of female vs male cadavers (p = 0.614). In three of the four cadavers in whom the unilateral absence of FT was verified, an accessory tendon in that side of the body was observed, in all cases with origin in the tendon of the extensor digitorum longus to the 5th toe. The present study confirms, for the Scottish population, the high prevalence of FT. These findings, in conjunction with its anatomical characteristics and its potential functional importance during gait in humans, would lead to considering FT as constant, being its absence a variation.